An overview af SAGE I and II ozone measurements - Mccormick, M. P.; Zawodny, J. M.; Veiga, R. E.; Larsen, J. C.; Wang, P. H. (1989)
The stratospheric Aerosol and Gas Experiments (SAGE) I and II measure Mie, Rayleigh, and gaseous extinction profiles using the solar occultation technique. These global measurements yield ozone profiles with a vertical resolution of 1 km which have been routinely obtained for the periods from February 1979 to November 1981 (SAGE I) and October 1984 to the present (SAGE II). The long-term periodic behavior of the measured ozone is presented as well as case studies of the observed short-term spatial and temporal variability. A linear regression shows annual, semiannual, and quasi-biennial oscillation features at various altitudes and latitudes which, in general, agree with past work. Also, ozone, aerosol, and water vapor data are described for the Antarctic springtime, showing large variation relative to the vortex. Cross-sections in latitude and altitude and polar plots at various altitudes clearly delineate the ozone hole vertically and areally.